Kappa Casein in Farm Animals: A Review - Ninan, Jacob; Vadodaria, V. P. (International Journal of Bio-resource and Stress Management, 2024)
A review of the results reported by different research workers has been compiled; with the aim to focus on various aspects encompassing the application of the important areas of research work on milk kappa casein. The major whey proteins in cow milk are alpha-lactalbumin and beta-lactoglobulin. Casein is a slow-digesting protein in contrast to whey protein that is rapid digesting. Milk Casein is of 3 or 4 types and each type has a similar structure but distinct molecules with different compositions, genetic variations, and functional properties. The main components of the cow milk casein complex are αs1 (CSN1S1), αs2 (CSN1S2), β (CSN2), and κ-caseins (CSN3) with each one of them occurring in two or more variants. Transgenic technologies could be used to alter milk composition in cows. Kappa-casein has been associated with differences in milk yield, composition and processing. Research work on casein has been attempted in different species (cow, buffalo, sheep, goat, horse, camel), yet it needs be extended to the remaining species and breeds of animals. The accurate and early identification of milk protein genotypes can have a direct impact on reviewing and developing dairy cattle breeding programs, to achieve the target of increasing production of milk and quality of its constituents on an economic footing. The review details the applied aspects of casein, classification and structure, polymorphism of kappa casein gene in different species of animals.